Leadership and ESG Implementation: An Empirical Study of their Influence on Financial Performance of Listed Companies in Indonesia - Hakim, Adam; Alfathan, Radiva; Dwidienawati, Diena (Jurnal Ilmiah Akuntansi & Bisnis, 2025)
The aim of this research is to determine the influence of ESG performance on financial performance and the influence of CEO Concern on sustainability on ESG performance. ESG Score is one of the important aspects that currently needs to be paid attention to by companies, because currently companies cannot only be oriented towards profitability but must also pay attention to aspects of sustainability. This research uses quantitative and qualitative approaches with secondary data collection methods using a total population of 79 public companies in Indonesia that have implemented ESG. This research uses SPSS 26 for quantitative regression analysis and Nvivo 14 for qualitative analysis. Findings reveal that the ESG score has an insignificant influence on Financial Performance and CEO Concern also does not have a significant influence on the ESG Score. This research contributes to research regarding the influence of ESG Score on Financial Performance and CEO Concern on Financial Performance in public companies in Indonesia. This research can be used by future researchers to theoretical implications and practical references in the study of Sustainability Finance.